The role of science and enlightenment in the works of Suleman Bakirgani - Avazova, Moxinur Toxirovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
Science and enlightenment are interpreted as central ideas in the works of Sulayman Bakyrgani (Hakim Ata). He continues the traditions of Yassawism and sees science not only as knowledge, but also as a spiritual and moral power that leads a person to perfection. Boqirgani influenced the hearts of the people to inculcate the principles of Islam and the ideas of Sufism through poetry. As we study his wisdom, we will witness that each of his wisdoms, as written by him, contains a gem. Sulayman Bakirgani wrote many spiritual and moral wisdoms and lyrical poems in "The Book of Bibi Maryam", "The Story of Ibrahim Halil", "The Book of the End Times" and other poems and epics. These examples of creativity influenced the rise of culture and spirituality of many peoples.